Research on Thermal Fatigue Mechanism and Test Profile Construction Method Based on Measured Temperature Data - CHEN Xin; WANG Peng (Kongzhi Yu Xinxi Jishu)
In order to truly reflect actual stress level borne by equipment, improve inherent reliability of product and reduce maintenance cost of product in the later period, in view of the problem that it is difficult to select test temperature level in the existing climate environment and reliability test standards, this paper analyzes thermal fatigue mechanism of products at measured ambient temperature and proposes a method for constructing test profiles. Through data processing, fatigue damage calculation and fatigue equivalence of the measured temperature data, test profile equivalent to the measured temperature data is finally obtained. Accelerated model is used to accelerate the equivalent test profile to obtain the accelerated test profile. Accelerated test results show that the error between test and computation results is 8.9%,which verifies the effectiveness of the proposed environmental test profile construction method based on measured temperature data.